Análise de eficiência nas cadeias curtas de abastecimento alimentar em Santa Terezinha de Itaipu - Rinaldi, André Renato (2022)
Short Food Supply Chains (SFSC) are attempts to bring the producer, or production site, closer to the final consumer, shortening or eliminating the links that permeate this path. In the municipality of Santa Terezinha de Itaipu, family farming is still heavily supported by the production of commodities, which generate little profit for the family farmer. However, some family farmers are diversifying, producing vegetables and accessing short marketing chains both in their municipality and in the surrounding area. These producers, despite having access to an advantageous market, may be subject to problems common to Brazilian agriculture: lack of financial organization; little diversification of sales strategies; structural problems on the property and problems related to plant health; environmental impacts caused by the production processes, and other difficulties that affect the productive, logistical, informational and environmental parts and cause the efficiency of rural activity to decline. These problems can generate inefficiency in your activity and your participation in short supply chains. There is still no clear methodology for measuring efficiency in agriculture, but attempts have been proposed, mainly based on financial or technical measurement. However, it is necessary that a method with a holistic view be applied to carry out an analysis of the efficiency of the participation of these family farmers in the short chains. Therefore, the general objective of this work is to analyze the efficiency of the short chains of vegetable family farmers in Santa Terezinha de Itaipu in four major pillars that cover several aspects: logistical-organizational efficiency; information efficiency; value distribution efficiency; and environmental efficiency. Producers in the organic production system achieved better average scores in all analyzed indicators. Producers in the integrated and conventional management systems had lower average scores that varied for each indicator presented. The organic system has different attributes in its production process that make it possible for its participation in short local food supply chains to be more efficient and more attractive to the local consumer, with a closer relationship with consumers, either physically, such as at street markets; whether in a virtual way, as in internet sales (e-commerce). The aspect of family succession showed low efficiency among all production processes, demonstrating that there are bottlenecks to be improved in the participation of these producers in short food supply chains. This efficiency assessment method provides an overview of the production process and the producer's participation in these local chains, and makes it possible to assess efficiency in environmental, value distribution, information and logistic-organizational aspects.